(untitled) (Eurasian Medical Research Periodical, 2023)
As a result of the study conducted, perexis oxidation activity against the background of the drug colostrum in patients with seborrheic dermatitis, Malassezia spp.ni, the quality of life dermatological index of patients was studied using questionnaires and a new treatment based on their result was recommended for dermatologists, cosmetologists. Case of acute seborrheic dermatitis among residents of Andijan region, quality of life dermatological index, perexis oxidation function, Malassezia spp. not examined, the effect of the drug colostrum has not been studied. Malassezia to the indications below in patients with seborrheic dermatitis spp.ni also, the change in the result of the action of the drug colostrum was studied for the first time.